Synovial sarcoma of the head and neck: Rare pathology, a therapeutic challenge - Álvarez, Alex (2021)
Objective: Synovial sarcomas are tumors of mesenchymal origin that can arise anywhere in the body. Sarcomas of the head and neck are uncommon, accounting for approximately 1 % of all malignant neoplasms in this location. It is a therapeutic challenge both for surgical resection and radiation therapy, given the morbidity and risk of injury to the structures adjacent to the tumor. The purpose of our case series is to share the experience of four patients treated with radiotherapy at Instituto Nacional de Cancerología, making a correlation of clinical, imaging, and histopathological presentation and the response to treatment. Methods: Four patients with a histologically confirmed diagnosis of synovial sarcoma of the head and neck treated with radiation therapy are described, emphasizing local control and treatment-associated morbidity reported on medical records. Results: Patients were between 21 and 48 years old (median 38 years), with male predominance. Two of the patients had hypopharyngeal involvement. Three patients had relapse-free survival between 4 to 6 years. One of the patients died due to disease progression during the first year of follow-up. Conclusion: We consider that our case series supports radiotherapy treatment in synovial sarcomas of the head and neck, showing local control at ups to 6 years, and it is an option for curative treatment, decreasing the probability of local recurrence with an adequate toxicity profile.